PENGARUH DOSIS PUPUK KCI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TERUNG (Solanum melongena L.) - Maryono; Nugraheni Hadiyanti; Supandji (Fakultas Pertanian Universitas Majalengka, 2022)
The use of KCl fertilizer in plant cultivation can improve soil fertility. KCl fertilizer can increase the growth and production of eggplant, both in quality and quantity. The purpose of this study was to determine the effect of the dose of KCl fertilizer on the growth and production of eggplant. This study is a one-factor trial using a completely randomized design (CRD). The factor tested was the dose of KCl fertilizer which consisted of 6 levels, namely: without KCl fertilizer (D0), 25 grams/plant (D1), 50 grams/plant (D2), 75 grams/plant (D3), 100 grams/plant (D4), 125 grams/plant (D5). Each treatment was replicated 4 times, and each replication consisted of 2 plants. The observation variables in this study were plant height, number of leaves, leaf area, number of fruits per plant, fruit length per plant, wet weight, and dry weight of the plant. Observations of plant height and number of leaves were carried out when the eggplant plants were 14 DAP with an interval of 7 days until the vegetative growth ended. The treatment dose of KCl fertilizer had a significant effect on the growth and production of eggplant plants. Dosage of KCl 125 gr/plant resulted in the best growth seen in plant height and a higher number of leaves, respectively 88.00 cm and 37.00 fruit. The highest eggplant production at the dose treatment KCl fertilizer 125 g/plant seen in the number of fruit, fruit length, wet weight, and dry weight of fruit per plant each of 7 pieces; 19.92 cm; 1,152.97 grams and 228.04 grams.